Evidence for the presence of African swine fever virus in apparently healthy pigs in South-Kivu Province of the Democratic Republic of Congo - Bisimwa, P.N.; Machuka, Eunice M.; Githae, Dedan; Banswe, G.; Amimo, Joshua O.; Ongus, J.R.; Masembe, C.; Bishop, Richard P.; Steinaa, Lucilla; Djikeng, Appolinaire; Pelle, Roger (Elsevier, 2020)
African swine fever (ASF) is the most important disease constraining smallholder pig production in the Democratic Republic of Congo, causing high mortality in domestic pigs with severe impacts on the livelihoods of local populations. This study was conducted with the aim of determining the prevalence of ASF and circulating virus genotypes in asymptomatic pigs raised on smallholder farms in the South Kivu province to understand the transmission dynamics of ASF and ultimately improving disease control. A cross-sectional survey was carried out in 5 districts where 267 pig blood were screened for both antibody and viral genome using indirect Enzyme Linked Immunosorbent Assay (ELISA) and polymerase chain reaction (PCR) respectively. Additionally, amplicons from PCR positive samples were sequenced by Sanger method for genetic analysis of ASF virus (ASFV) based on the C-terminal region of the B646L gene that encodes the major capsid protein p72 and the gene E183L encoding the p54 protein. The overall seroprevalence obtained based on antibody to p30 protein was 37 % and was significantly higher (P < 0.05) in adult (>1 year) animals (44.7 %) than in younger (<1 year) ones (33.5 %). Moreover, the seropositivity varied significantly (P < 0.05) according to the pig husbandry system practiced within the districts investigated with Uvira (55 %) and Mwenga (42.2 %) having the highest ASFV antibodies, while the lowest (10.5 %) were in Kalehe. Free-range pigs exhibited a higher level of seropositivity to ASFV antibody (68.9 %) than pigs kept in the pigsty housing system (21.6 %). However, no statistically significant differences (P > 0.05) were observed when sex of the animal and breed were factored. PCR detection of ASFV amplified a specific band of expected size (257 bp) in 61 out of 267 blood samples, confirming the presence of the viral DNA in 22.8 % of asymptomatic domestic pigs. Statistical analysis revealed that ASFV infection in domestic pigs varied significantly (p < 0.001) according to geographical location and breed, with the highest infection rate found in Walungu district (33.7 %) while the lowest was registered in Kalehe (15.8 %). Local pigs (27.2 %) were more infected than crosses (9.2 %). Phylogenetic analyses based on partial sequences of the p72 and p54 genes revealed that all the ASFV detected belonged to genotype IX, which has previously been reported in other parts of DR Congo, and was clustered together with isolates from Kenya, Uganda and Republic of Congo. This study avails the first evidence of the presence of ASF virus in domestic pigs in the absence of outbreaks in South Kivu province, eastern DR Congo, indicating a need to raise awareness among pig farmers and veterinary authorities on the application of biosecurity measures and good husbandry practices to control the disease.